2016
DOI: 10.1155/2016/9523251
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Control Strategy of Shifting Time Involving Multigroup Clutches

Abstract: This paper focuses on the control strategy of shifting time involving multigroup clutches for a hydromechanical continuously variable transmission (HMCVT). The dynamic analyses of mathematical models are presented in this paper, and the simulation models are used to study the control strategy of HMCVT. Simulations are performed in SimulationXplatform to investigate the shifting time of clutches under different operating conditions. On this basis, simulation analysis and test verification of two typical conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Rossetti and Macor 49 put forward multi-objective optimization focused on better efficiency as well as other factors, such as smaller size. They took a co-simulation approach, as shown in Figure 6 50 , combining the Multi-Objective Particle Swarm Optimizer algorithm in MATLAB (The MathWorks, Natick, MA) and established the system model in AMESim (Siemens PLM Software, Plano, TX), transmitting the AMESim result to MATLAB after several iterations to get the Pareto optimization result. Through this method, they found that the input coupled transmission was suitable for small displacements, while the output coupled transmission was suitable for large displacements.…”
Section: Key Technologies Status and Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rossetti and Macor 49 put forward multi-objective optimization focused on better efficiency as well as other factors, such as smaller size. They took a co-simulation approach, as shown in Figure 6 50 , combining the Multi-Objective Particle Swarm Optimizer algorithm in MATLAB (The MathWorks, Natick, MA) and established the system model in AMESim (Siemens PLM Software, Plano, TX), transmitting the AMESim result to MATLAB after several iterations to get the Pareto optimization result. Through this method, they found that the input coupled transmission was suitable for small displacements, while the output coupled transmission was suitable for large displacements.…”
Section: Key Technologies Status and Trendsmentioning
confidence: 99%
“…Pan et al 33 and Zhu et al 50 studied the effects of physical parameters (engine rotating speed, load torque, main circuit pressure, and speed valve flow rate) and shift time on shift quality. Shift time had previously always been ignored, because it played a limited role in a few clutch systems.…”
Section: Key Technologies Status and Trendsmentioning
confidence: 99%
“…Furthermore, some researchers optimized the shifting process of automatic transmission in other ways, such as minimizing the jerk 11 and reducing greenhouse gas emission. 12 Other researchers presented dynamic analyzes of mathematical models that were used to study the control strategy of hydromechanical continuously variable transmission (HMCVT) 13 to improve shifting quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the control of HMT, Savaresi et al [20,21] designed a controller for a six-range power split continuous variable transmission. Zhu et al [22,23] studied the control strategy for a seven-range HMT based on the shifting time. Cheong et al [24,25] studied the control of hydromechanical hydraulic hybrid vehicles.…”
Section: Introductionmentioning
confidence: 99%